Pengaruh Fanatisme terhadap Emosi: Studi Fenomenologi terhadap Fanatisme Fans FC Barcelona Pengikut Akun Instagram @fansbarcaid_ - Mochammad Helmy Fikri; Nadia Ayu Fadhilah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Fanaticism towards football clubs has become a phenomenon with significant impacts on their supporters' social and psychological aspects. This study aims to identify how fanaticism towards FC Barcelona influences the emotions of its fans, particularly followers of the Instagram account @fansbarcaid_. Using a qualitative phenomenological approach, the study explores the emotional experiences of fans through in-depth interviews with the account's followers. The findings reveal that fanaticism contributes to various emotional responses, including long-lasting loyalty to the team, emotional attachment during victories and defeats, and emotional and material support for the team. This research provides deeper insights into the relationship between sports fanaticism and the emotional dynamics of fans, particularly the dynamics of fanaticism within the football context. The fanaticism of @fansbarcaid_ followers towards FC Barcelona fosters profound loyalty and significant emotional attachment.